How suitable is the gold-labelling method for the quantification of nanoplastics in natural water? - Februriyana Pirade; Kim Maren Lompe; Javier Jiménez-Lamana; Sulalit Bandyopadhyay; Katharina Zürbes; Nesrine Bali; Dušan Materić; Jan Willem Foppen (Aqua, 2023)
Nanoplastics are detected in surface water, yet accurately quantifying their particle number concentrations remains a significant challenge. In this study, we tested the applicability of a gold-labelling method to quantify nanoplastics in natural organic matter (NOM) containing water matrices. Gelatin-coated gold nanoparticles (Au-gel NPs) form conjugates with nanoplastics via electrostatic interaction which produces peak signals which can be translated into particle number concentration using single-particle inductively coupled plasma–mass spectrometry (SP-ICP-MS). We used water samples with various NOM concentrations, with and without the addition of 1 × 107 particle–1 nanoplastics. Our results indicate that nanoplastics in low NOM samples (<1 mg·C L−1) could be successfully quantified. However, in high NOM samples (>15 mg·C L−1), only 13–19% of added nanoplastics were successfully quantified. Further digestion to remove NOM yielded only 10% of spiked nanoplastics. This discrepancy in high NOM samples could likely be attributed to the competition between nanoplastics and NOM existing in the water sample to bind with Au-gel NPs. Our study highlights the suitability of the Au-gel labelling method for quantifying nanoplastics in low NOM water samples. Nevertheless, further optimization, including pre-digestion steps, is essential to apply this method for high NOM water samples effectively. HIGHLIGHTS Quantification of nanoplastic with gold-labelling using single-particle ICP-MS.; Application of nanoplastic labelling in natural waters.; Underestimation of nanoplastic due to competing negatively charged NOM.; Inefficient digestion to remove NOM.;